An assessment of the Isoniazid preventative therapy programme for children in a busy primary healthcare clinic in Nelson Mandela Bay, Eastern Cape Province - Tucker, Faye Bronwyn (Department of Paediatrics and Child Health, 2015)
Introduction: Tuberculosis is the second leading cause of death from an infectious cause worldwide having claimed approximately 1.5 million lives in 2013. Estimates suggest that children account for about six percent of the total number of TB cases globally, however in South Africa this figure is much higher (15%). Young children are at particularly high risk of mortality and significant morbidity from TB. Despite clear evidence that Isoniazid preventative therapy (IPT) can reduce the risk of progression from TB infection to disease, IPT has been a poorly implemented component of national TB control programmes, especially in high TB-burden areas, including South Africa. This study aims to determine current practices regarding the identification and management of child contacts < 5 years in an area with an extremely high TB incidence rate where little background data exists on the topic. It will also assess the operational aspects of the TB control programme relating to the spread of TB to children. Methodology: A cross-sectional descriptive study was conducted using a retrospective review of clinic records from infectious index patients aged ≥15 years at West End clinic in the Nelson Mandela Bay health district in the Eastern Cape Province. A sample size of 246 child contacts (<5 years) was required to obtain a 95% confidence index with a 5% precision. This is based on 20% of eligible child contacts < 5years receiving IPT, as described by van Wyk, et al. (2010). 491 Index patient records were assessed in order to identify 261 child contacts < 5 years of age. Results: Contacts were generally well recorded with only 12.5% of index patient folders having no contacts documented although only 0.53 child contacts <5years were identified per index patient. A total of 261 child contacts < 5 years were identified and of these 184 (70.5%) were screened for TB. Two contacts were started on TB treatment and 108/184 (58.7%) were initiated on TB prevention therapy. For the remaining 74 (40.2%) children who were screened there was no documentation of further management. Adherence to IPT was extremely poor with only 4 (3.7%) children who started TB prevention completing the 24 week course. Female index patients were more likely to have contacts documented and to bring their contacts for screening. Contacts of index 16 patients who had previous TB were less likely to be screened and initiated on TB prevention therapy. The results of the assessment of programmatic factors relating to childhood TB control showed that patients were diagnosed and were rapidly initiated on treatment (median time of 5 days from sputum collection to commencement of treatment). It took a median of 4 days for children to be screened once the index patient had started treatment and a further 2 days (median) for child contacts < 5 years to be initiated on preventative therapy. Conclusion and recommendations: The results of this study are in keeping with those obtained in other settings with a high burden of TB. Although the documentation of contacts in this setting was relatively good, child contacts < 5 years were poorly identified and the fall-out of children at each step from identification to preventative treatment completion was still unacceptably high. Contacts of men and retreatment index patients are at particularly high risk of poor management. Recommendations are made for interventions at national and local level to improve contact management and the documentation thereof.